Prenatal diagnosis of choledochal cyst: A case report - Fuanglada Tongprasert (2018)
Choledochal cyst is one of the intra-abdominal abnormalities of the biliary ducts that present as a cystic mass in the right upper quadrant abdomen. Prenatal diagnosis has been achieved by the demonstration of a connection between a dilated common bile duct and a cystic lesion. In this report, we describe a pregnant woman in whom routine fetal anomaly scan strongly suggested a choledochal cyst at 29 weeks of gestation by demonstrating a round cystic mass in the right upper quadrant of the abdomen, completely separated from the stomach, bowel loops, and gall bladder, and which showed a connection with the dilated common bile duct. © 2011 Wiley Periodicals, Inc.